Built environment auditing, active mobility and children’s wellbeing - Babb, Courtney William (Curtin University, 2014)
This thesis explores how planners can facilitate children’s wellbeing through auditing the urban environment for active travel. The findings reveal that audits have the potential to address critical issues regarding the quality of the built environment around schools. Further, children were found to be effective evaluators of their school environment. Auditing can be improved by highlighting the sensory qualities of the built environment and using audits strategically to adapt to the policy context of school environments.